Efficacy and safety of Mydriatic Microdrops for Retinopathy Of Prematurity Screening (MyMiROPS): study protocol for a non-inferiority crossover randomized controlled trial - Aikaterini K. Seliniotaki; Anna-Bettina Haidich; Maria Lithoxopoulou; Helen Gika; Eleftheria Boutou; Christina Virgiliou; Martha Nikolaidou; Aristides Dokoumetzidis; Nikolaos Raikos; Elisavet Diamanti; Nikolaos Ziakas; Asimina Mataftsi (Trials, 2022)
Abstract Background Retinopathy of prematurity (ROP) eye examination screening presupposes adequate mydriasis for an informative fundoscopy of preterm infants at risk, on a weekly basis. Systemic absorption of the instilled mydriatic regimens has been associated with various adverse events in this fragile population. This report aims to present the fully developed protocol of a full-scale trial for testing the hypothesis that the reduced mydriatic drop volume achieves adequate mydriasis while minimizing systemic adverse events. Methods A non-inferiority crossover randomized controlled trial will be performed to study the efficacy and safety of combined phenylephrine 1.67% and tropicamide 0.33% microdrops compared with standard drops in a total of 93 preterm infants requiring ROP screening. Primary outcome will be the pupil diameter at 45 (T45) min after instillation. Pupil diameter at T90 and T120 will constitute secondary efficacy endpoints. Mixed-effects linear regression models will be developed, and the 95% confidence interval approach will be used for assessing non-inferiority. Whole blood samples will be analyzed using hydrophilic liquid chromatography–tandem mass spectrometry method (HILIC–MS/MS), for gathering pharmacokinetic (PK) data on the instilled phenylephrine, at nine specific time points within 3 h from mydriasis. Pooled PK data will be used due to ethical restrictions on having a full PK profile per infant. Heart rate, oxygen saturation, blood pressure measurements, and 48-h adverse events will also be recorded. Discussion This protocol is designed for a study powered to assess non-inferiority of microdrops compared with standard dilating drops. If our hypothesis is confirmed, microdrops may become a useful tool in ROP screening. Trial registration ClinicalTrials.gov NCT05043077 . Registered on 2 September 2021